Extensive phospholipid resorption from senescing leaves is not associated with phospholipid substitution in an oligotrophic heath - Grace H. Liang; Orpheus M. Butler; Charles R. Warren (Plant and Soil, 2026)
Background and aims In leaves, ~ 25% of phosphorus (P) is allocated to membrane phospholipids. A significant amount of leaf P is resorbed during leaf senescence to reduce plant P loss upon leaf abscission and fuel the growth of new leaves. High P resorption observed in plants on P depleted soils has been associated with extensive resorption of all P-fractions, including phospholipids, from senescent leaves. This high resorption of phospholipid-P could be associated with the substitution of phospholipids with non-P galactolipids and sulfolipids. Methods We evaluated whether high phospholipid resorption is associated with the substitution of phospholipids with non-P lipids by quantifying the total P, and intact membrane phospholipid, galactolipid and sulfolipid concentrations of mature and senescent leaves of nine co-occurring species (five families) associated with a severely P-poor soil in eastern Australia. Results Phosphorus resorption efficiency, defined as the percentage of P resorbed from senescing leaves per P content in mature leaves, was high across species ( c. 77 – 96%). Total membrane lipid content was substantially lower in senescent leaves than mature leaves across species, although, there was a tendency for resorption efficiency to be greater for non-P lipids ( c. 55 – 95%) than phospholipids ( c. 4 – 87%). Conclusion Exceptionally high rates of total and phospholipid P resorption from senescing leaves is not necessarily associated with the substitution of phospholipids with non-P lipids.

Corrigendum to “Improving lipid utilization and growth through lecithin inclusion in diets for giant grouper (Epinephelus lanceolatus)” [Anim. Feed Sci. Technol. 326 (2025) 116393] - Grace Butler; Caroline Lourdes Candebat; Simon Kumar Das; Leo Nankervis (Animal Feed Science and Technology, 2025)

Improving lipid utilization and growth through lecithin inclusion in diets for giant grouper (Epinephelus lanceolatus) - Grace Butler; Caroline Lourdes Candebat; Simon Kumar Das; Leo Nankervis (Animal Feed Science and Technology, 2025)

Dietary methionine and choline mediate mobilisation of plasma lipids to improve feed efficiency for the diets of giant grouper (Epinephelus lanceolatus) - Grace Butler; Caroline Lourdes Candebat; Simon Kumar Das; Leo Nankervis (Animal Feed Science and Technology, 2025)

Lipid profiles of plants and soil microbial communities are shaped by soil parent material in Australian sclerophyll forests - Grace H. Liang; Orpheus M. Butler; Charles R. Warren (Plant and Soil, 2024)
Background and aims Plant and soil microbes can reduce their phosphorus (P)-requirements by replacing phospholipids with non-P containing lipids (e.g., galactolipids, sulfolipids, and betaine lipids). There have been few studies of this process in the field (i.e., in natural ecosystems); thus, it is unclear whether a similar replacement of phospholipids with non-P lipids occurs across natural gradients of soil P-availability. Methods We compared the membrane lipid profiles of plant leaves, roots, and soil microbial communities between two adjacent native Australian sclerophyll forest ecosystems—one situated on a severely P-deficient sandstone-derived soil and the other on a comparatively P-rich shale-derived soil. The herbaceous species, Lomandra longifolia, which occurred across both soils was sampled, along with two Myrtaceae tree species associated with each soil type. Results The phospholipid content of plant leaves and soil microbes was two- to three-fold greater in the shale site than the sandstone site, but non-P lipid content did not differ between sites. Conclusion Our results indicate that plants and soil microbes can have a lower investment of P into phospholipids in response to P-deficiency without a concomitant increase in non-P lipid content. Modulations in phospholipid concentration occurred across all plant- and soil microbial-associated phospholipid classes.

Annual variation in soil respiration and its component parts in two structurally contrasting woody savannas in Central Brazil - Andre Butler; Patrick Meir; Gustavo Saiz; Leandro Maracahipes; Beatriz Schwantes Marimon; John Grace (Plant and Soil, 2012)